175k views
0 votes
Please help soon!!! I can’t figure this out! ;-; I just need this answer :(

Please help soon!!! I can’t figure this out! ;-; I just need this answer :(-example-1
User JTaub
by
6.2k points

1 Answer

1 vote
10^2 + 4 * (6 + 3) - 27 ÷ (9 - 6) = 127

=100 + 4 * 9 - 27 ÷ 3
multiplication & division before addition and subtraction (order of operations rules, PEMDAS)

100 + 36 - 9= 127
136 - 9= 127
127= 127

Place a set of parentheses around (6+3) and (9-6).

Hope this helps! :)
User ZZB
by
6.3k points